2004
DOI: 10.1002/anie.200460172
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Apoptolidin

Abstract: A ring‐size‐selective macrolactonization and the early introduction of the saccharide portions are the main features of a total synthesis of the 20‐membered macrolide apoptolidin (see formula), which induces apoptosis in rat glia cells transformed with oncogenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Syntheses of apoptolidinone A, the aglycone of 1, were reported by the groups of Sulikowsky [143], Crimmins [144], Nicolaou [138][139][140], and Koert [141,142]. In addition, several studies on the synthesis of fragments of apoptolidinones have been reported [137,[145][146][147][148][149][150][151][152][153][154][155].…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Syntheses of apoptolidinone A, the aglycone of 1, were reported by the groups of Sulikowsky [143], Crimmins [144], Nicolaou [138][139][140], and Koert [141,142]. In addition, several studies on the synthesis of fragments of apoptolidinones have been reported [137,[145][146][147][148][149][150][151][152][153][154][155].…”
Section: Methodsmentioning
confidence: 97%
“…Successful total synthesis of 1 has been achieved by the groups of Nicolaou [138][139][140] and Koert [141,142]. Syntheses of apoptolidinone A, the aglycone of 1, were reported by the groups of Sulikowsky [143], Crimmins [144], Nicolaou [138][139][140], and Koert [141,142].…”
Section: Methodsmentioning
confidence: 99%
“…Total synthesis of apoptolidin (90), a metabolite of Nocardiopsis sp. which displayed potent antitumor activities, was accomplished by several research groups via a similar glycosyl sulfoxide method (Scheme 21) [123][124][125]. In Nicolaou's synthesis, coupling of the complex alcohol 92 with sulfoxide 91 was performed in the presence of Tf 2 O (2.5 equiv.)…”
mentioning
confidence: 99%
“…[5] In 2001 Koert reported the synthesis of apoptolidinone [6] and later the same year Nicolaou described the total synthesis of apoptolidin. [7] Three years later the Koert group described the total synthesis of apoptolidin [8] and our group reported the second synthesis of the aglycon apoptolidinone. [9] The first total synthesis of apoptolidin reported by the Nicolaou group [7] and other recent work [10] demonstrated apoptolidin to be a rather labile compound that undergoes a base-induced acyl migration from a hydroxy group located at C19 to the neighboring C20 hydroxy group to produce isoapoptolidin (3), a compound possessing diminished activity against mitochondrial F 0 F 1 -ATPase.…”
Section: Introductionmentioning
confidence: 99%